Adaptive coordination assemblies based on a flexible tetraazacyclododecane ligand for promoting carbon dioxide fixation. Issue 31 (18th July 2022) - Li, Shaochuan; Liu, Caiping; Chen, Qihui; Jiang, Feilong; Yuan, Daqiang; Sun, Qing-Fu; Hong, Maochun
Abstract : A series of coordination hosts were prepared and their applications in CO2 fixation were studied. Abstract : Coordination hosts based on flexible ligands have received increasing attention due to their inherent adaptive cavities that often show induced-fit guest binding and catalysis like enzymes. Herein, we report the controlled self-assembly of a series of homo/heterometallic coordination hosts (Me4 enPd)2 n (ML ) n [ n = 2/3; M = Zn(ii )/Co(ii )/Ni(ii )/Cu(ii )/Pd(ii )/Ag(i ); Me4 en: N, N, N ′, N ′-tetramethylethylenediamine] with different shapes (tube/cage) from a flexible tetraazacyclododecane-based pyridinyl ligand (L ) and cis -blocking Me4 enPd(ii ) units. While the Ag(i )-metalated ligand (AgL ) gave rise to the formation of a (Me4 enPd)4 (ML )2 -type cage, all other M(ii ) ions led to isostructural (Me4 enPd)6 (ML )3 -type tubular complexes. Structural transformations between cages and tubes could be realized through transmetalation of the ligand. The buffering effect on the ML panels endows the coordination tubes with remarkable acid–base resistance, which makes the (Me4 enPd)6 (ZnL )3 host an effective catalyst for the CO2 to CO3 2− conversion. Control experiments suggested that the integration of multiple active Zn(ii ) sites on the tubular host and the perfect geometry match between CO3 2− and the cavity synergistically promoted such a conversion. Our results provide an important strategy for the design of adaptive coordination hosts to achieve efficient carbon fixation.